Analysis of daytime medium-scale traveling ionospheric disturbances by two-dimensional maps of total electron content perturbation and ionograms - R.O. Sherstyukov; A.D. Akchurin (Учёные записки Казанского университета: Серия Физико-математические науки)
To analyze midlatitude medium-scale traveling ionospheric disturbances (MSTIDs), the sufficiently dense network of GNSS receivers (more than 150 ground-based stations) have been used. For the first time, daytime MSTIDs in the form of their main signature (band structure) on high-resolution two-dimensional maps of the total electron content perturbation (TEC maps) have been compared with ionosonde data with a high temporal resolution. For a pair of events, a relationship between southwestward TEC perturbations and evolution of F2 layer traces has been established. So, F2 peak frequency varied in antiphase to TEC perturbations. The ionograms show that during the moving of plasma depletion band (overhead ionosonde) the F2 peak frequency is the highest, and vice versa, for the plasma enhancement band, the F2 peak frequency is the lowest. One possible explanation may be a greater inclination of the radio beam from the vertical during the placement of a plasma enhancement band above the ionosonde, as evidenced by the absence of multiple reflections and the increased occurrence rate of extra cusp trace. Another possible explanation may be the redistribution of the electron content in the topside ionosphere with a small decrease in the F peak concentration of the layer with a small increase in TEC along the line-of-sight. The analysis of F2 peak frequency variation has shown that the observed values of TEC perturbations equal to 0.4 and 0.8 TECU correspond to the values of ΔN/N equal to 10% and 25%. The need for further research is evident.